The digital Re-educate project. A testimony. - Benussi, Fulvio Oscar; Capezzuoli, Alessandro (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The Re-educo project included, in its initial phase, research to contextualise the state with respect to the spread of digitisation and the skill mismatch of European workers. Then, several seminars addressed to secondary school students were realised. The two Italian partners, Link Campus University and Italian Digital Revolution carried out six information seminars, two orientation seminars and two trainings during 2021. The text below concerns two information seminars and one of the trainings that the student, who wrote the report, attended with his third grade class at the Allende High School in Milan. After the student’s testimony, the trainers of the relevant seminars offer their reflections on the and some notes on the contents, teaching methods and tools used.